Reading the Social Sciences Theologically (Part 1): Approaching and Qualifying Models of Human Development - Trentham, John David (Christian education journal, 2019)
Part 1 of 2. This series of articles seeks to present a viable hermeneutical framework according to which Christian scholars and educators may read social scientific literature with theological clarity. Part 1 establishes the manner in which Christians may profitably approach and qualify social science models of human development. The "principle of inverse consistency," introduced at the conclusion of this article, is put forth as a conceptual tool for interpreting developmental models with confessional and intellectual virtue.